SAT0341 PREDICTORS TO PROGRESSION TO SYSTEMIC SCLEROSIS IN A GROUP OF SECONDARY RAYNAUD PHENOMENON OBSERVED IN A LARGE SINGLE BRAZILIAN COHORT. (2nd June 2020) - Siqueira, V.; Helbingen, M.; Luppino-Assad, A. P.; Carriço Da Silva, H.; Andrade, D.; Medeiros-Ribeiro, A. C.; Sampaio-Barros, P. D.
Abstract : Background: The 2013 ACR/EULAR classification criteria for systemic sclerosis (SSc) allowed the inclusion of a subset of patients without skin involvement, emphasizing the need of early diagnosis of SSc. Objectives: In this setting, the objective of this study was to classify, according to ACR/EULAR SSc criteria, patients with Raynaud phenomenon (RP) and at least one SSc manifestation, except for skin involvement, and analyze predictors for development of SSc. Methods: This is a cross-sectional single-center analysis of consecutive patients presenting RP and a characteristic SSc manifestation (SSc autoantibody, SSc visceral involvement or SD pattern at nailfold capillaroscopy - NFC), without skin involvement, who attended a scleroderma outpatient clinic between 2010 and 2019. Patients were classified as SSc (according to ACR/EULAR SSc criteria) or undifferetiated connective tissue disease (UCTD) in their last medical visit and compared. Additionally, a longitudinal retrospective analysis of both groups was performed to find predictors for development of SSc. Data were obtained from an electronic register database. Statistical significance was set up as p<0.05. Results: Among 217 patients, 153 (70.5%) were classified as SSc, at the last medical visit, including 65 (30%) after the first investigation. During a comparable median follow-up [4.9±3.8 vs. 4.6±3.0 years;p=0.90], patients with SSc presented more frequently puffy fingers (PF:73% vs. 6.3%;p<0.01), pitting scars (87.4% vs. 4.7%;p<0.01), digital ulcers (25.2% vs. 1.6%;p<0.01), telangiectasias (52.3% vs. 7.8%;p<0.01), interstitial lung disease (ILD:66.7% vs. 34.4%;p<0.01), pulmonary hypertension (PH:18.3% vs. 7.9%;p=0.049) and esophageal dismotility (ED: 58.9% vs. 43.8%:p=0.02) than secondary RP patients without SSc. Moreover, SSc patients had more SD pattern at NFC (83.4% vs . 57.8%;p<0.01), anti-Scl70 antibody (16.6% vs . 3.1%;p<0.01), and nucleolar ANA pattern (22.5% vs . 10.9%;p=0.048). Furthermore, SSc patients were more frequently treated with immunosuppressive therapy (80.1% vs . 37.5%;p<0.01) and presented an increased death rate (9.9% vs . 1.6%;p<0.01 and Figure 1). For the analysis of the predictors to SSc, patients who had already fulfilled SSc criteria at baseline were excluded and 152 patients were analysed: 88 progressed to SSc and 64 remained as UCTD. After multivariate analyses, puffy fingers (OR=4.48; 95%CI 1.17-17.17;p=0.029) and a higher SSc score, both at baseline, (OR: 1.97; 95%CI 1.33-2.92;p<0.001) were predictors to SSc, while esophageal symptoms (OR=0.18; 95%CI 0.05-0.67; p=0.01) and absence of clinical symptoms (OR=0.08; 95%CI 0.01-0.40; p=0.002) were negative predictive factors. When analyzing the combination of SSc features, RP + PF + positive ANA (OR=15.5; 95%CI 4.5-53.1;p<0.001), RP + PF + positive ANA + SD-NFC (OR=12.3; 95%CI 2.8-54.2;p<0.001), RP + PF + SD-NFC (OR=12; 95%CI 2.79-54.1;p<0.01), and RP + lung disease (ILD/HAP) + SD-NFC (OR=3.0; 95%CI 1.1-10.5;p<0.04) were associated with classification as SSc, while combinations without non-RP clinical symptoms, as RP + SD-NFC (OR=0.027; 95%CI 0.003-0.210;p<0.001) and RP + anticentromere + SD-NFC (OR=0.050; 95%CI 0.007-0.440;p<0.001) were not associated with SSc. Conclusion: Among patients with RP and SSc features, but without skin involvement, those with SSc had a more severe disease with worse prognosis than UCTD with RP. Puffy fingers and a higher baseline SSc score, especially in combinations including PF or lung disease were predictors of SSc, reinforcing the strength of the ACR/EULAR classification criteria and the presence of specific non-RP symptoms. Disclosure of Interests: Valdirene Siqueira: None declared, Mariely Helbingen: None declared, Ana Paula Luppino-Assad: None declared, Henrique Carriço da Silva: None declared, Danieli Andrade: None declared, Ana Cristina Medeiros-Ribeiro: None declared, Percival D. Sampaio-Barros Consultant of: Abbvie, Boehringer Ingelheim, Lilly, Novartis, Speakers bureau: Abbvie, Janssen, Lilly, Novartis